REVIEW JURNAL: POTENSI DAN MASALAH DALAM PENGEMBANGAN KEMANDIRIAN BAHAN BAKU OBAT TRADISIONAL DI INDONESIA - Ristagari, Fannesia; Ilfa Zahara Arkhan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The use of herbs for health purposes has been widely practiced since thousands of years ago prior to the discovery of synthetic chemical drugs. Indonesia is widely known for having a large biodiversity about 30,000 species of plants which is equal to 75% of the total number of plants in the world so that Indonesia is known as a mega-center of world biodiversity. This fact emphasize that Indonesia has enormous potential in the traditional medicine industry that can compete at the world level. However, in the development of traditional raw materials and the production of traditional medicines, there are several problems that can prevent the growth of the traditional medicine industry including herbal raw materials that do not meet the requirements, the business climate is not conducive, the technology development of the production of extract raw materials is still low, uneven distribution of third parties in the territory of Indonesia which making it difficult for medium and small industries that experience limited facilities for product testing, the exclusion of traditional medicines in the JKN program and the lack of empirical evidence from plants that have potential as traditional medicines.